Lactic acid fermentation of human excreta for agricultural application. (15th January 2018) - Andreev, Nadejda; Ronteltap, Mariska; Boincean, Boris; Lens, Piet N.L.
Abstract: Studies show that source separated human excreta have a fertilizing potential with benefits to plant growth and crop yield similar or exceeding that of mineral fertilizers. The main challenges in fertilizing with excreta are pathogens, and an increased risk of eutrophication of water bodies in case of runoff. This review shows that lactic acid fermentation of excreta reduces the amount of pathogens, minimizes the nutrient loss and inhibits the production of malodorous compounds, thus increasing its agricultural value. Pathogens (e.g., Enterobacteriacea, Staphylococcus and Clostridium ) can be reduced by 7 log CFUg −1 during 7–10 days of fermentation. However, more resistant pathogens (e.g. Ascaris ) are not always efficiently removed. Direct application of lacto-fermented faeces to agriculture may be constrained by incomplete decomposition, high concentrations of organic acids or insufficient hygienization. Post-treatment by adding biochar, vermi-composting, or thermophilic composting stabilizes and sanitizes the material. Pot and field experiments on soil conditioners obtained via lactic acid fermentation and post treatment steps (composting or biochar addition) demonstrated increased crop yield and growth, as well as improved soil quality, in comparison to unfertilized controls. Graphical abstract: Image 1 Highlights: Lactic acid fermentation and biochar improve agricultural value of human excreta. The pathogens are reduced by 7–10 log CFU after 7–10 days of lacto-fermentation. Excreta acidification by lacto-fermentation reduces ammonia emissions and odour. Agricultural use requires combined lacto-fermentation and thermophilic composting.